Character Education Management Through the Little Police Officer (Pocil) Program at TK Kemala Bhayangkari 31 Tanggul - Rizal, Ahmad Fahrul; Widiatsih, Asri; Wijaya, Pipit Rika (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study examines character education management through the Little Police Officer (Pocil) Program at TK Kemala Bhayangkari 31 Tanggul. The focus is on the program’s effectiveness in shaping the character traits of discipline, responsibility, and independence in early childhood. A qualitative approach with a case study method was used. Data collection techniques included direct observation, in-depth interviews, and document analysis. All data were analyzed using Miles and Huberman’s analysis model. The study found that systematic planning, implementation, and evaluation processes contributed significantly to the program’s success. Supporting factors such as school commitment and partnerships with the police, as well as inhibiting factors such as limited time and resources, were identified. Positive impacts were observed in the improvement of children’s discipline, responsibility, cooperation, and independence.